Treatment of 200 Locally Advanced (Stage III) Pancreatic Adenocarcinoma Patients With Irreversible Electroporation. Issue 3 (September 2015) - Martin, Robert C. G.; Kwon, David; Chalikonda, Sricharan; Sellers, Marty; Kotz, Eric; Scoggins, Charles; McMasters, Kelly M.; Watkins, Kevin
<x xml:space="preserve">Abstract</x> Objectives: Ablative therapies have been increasingly utilized in the treatment of locally advanced pancreatic cancer (LAPC). Irreversible electroporation (IRE) is an energy delivery system, effective in ablating tumors by inducing irreversible membrane destruction of cells. We aimed to demonstrate efficacy of treatment with IRE as part of multimodal treatment of LAPC. Methods: From July 2010 to October 2014, patients with radiographic stage III LAPC were treated with IRE and monitored under a multicenter, prospective institutional review board–approved registry. Perioperative 90-day outcomes, local failure, and overall survival were recorded. Results: A total of 200 patients with LAPC underwent IRE alone (n = 150) or pancreatic resection plus IRE for margin enhancement (n = 50). All patients underwent induction chemotherapy, and 52% received chemoradiation therapy as well for a median of 6 months (range, 5–13 months) before IRE. IRE was successfully performed in all patients. Thirty-seven percent of patients sustained complications, with a median grade of 2 (range, 1–5). Median length of stay was 6 days (range, 4–36 days). With a median follow-up of 29 months, 6 patients (3%) have experienced local recurrence. Median overall survival was 24.9 months (range: 4.9–85 months). Conclusions: For patients with LAPC (stage III), the addition of IRE to conventional chemotherapy and radiation therapy results in substantially prolonged survival compared with historical controls. These results suggest that ablative control of the primary tumor may prolong survival.